Real Time Sorting of Plastic Recyclables Using an FPGA based SVM - House, Bryan W. (My University, 2011)
The amount of recyclable material being processed worldwide is increasing. There is a demand for new technologies that can quickly sort these materials for maxi-mum purity while maintaining high throughput. This thesis proposes a method toautomatically sort two materials: Polycoat containers and Polyethylene terephtha-late (PET) bottles. This method utilizes a visible light camera and does not relyon Near-Infrared spectrometry. A high-speed method to automatically locate re-gions that likely contain these materials within the image and remove them from thebackground is presented. These regions are merged into whole containers and are classified as either a Polycoat container or PET bottle. This is accomplished using alinear support vector machine (SVM) trained on the histogram of pixel intensities. Anovel graph theoretic based region growing technique is proposed and experimental results are provided to characterize the system. The proposed method obtained a93% recognition rate while running in real-time on an FPGA.
Keywords: FPGA; Computer Vision; Machine Learning; SVM; Recycling; Signal Processing; VLSI and circuits, Embedded and Hardware Systems; Signal Processing